Interpreting global variations in the toll of COVID-19: The case for context and nuance in hypothesis generation and testing - Stein, Roger M.; Katz, David L. (Frontiers in Public Health, 2022)
As of January 2022, the COVID19 pandemic remains on-going, affecting populations worldwide. The potential risks of the Omicron variant (and future variants) still remain an area of active investigation. Thus, the ultimate human toll of SARS-CoV-2, and, by extension, the variations in that toll among diverse populations, remain unresolved. Nonetheless, an extensive literature on causal factors in the observed patterns of COVID19 morbidity and mortality has emerged – particularly at the aggregate level of analysis. This article explores potential pitfalls in the attribution of COVID outcomes to specific factors in isolation by examining a diverse set of potential factors and their interactions.